Human Resource Management (Human Resource Planning) - Cappelletti Chiara; Valenti Diego; Saresella Mara (Sharia Oikonomia Law Journal, 2023)
Human resource planning is the first thing an organization or company must do when a company seeks better human resource management. All organizations or companies must determine their future with different plans according to the demands of the times. Nowadays changes are rapid, so organizations or companies must be able to keep up with changes quickly and precisely. Organizations or companies must be able to anticipate and adapt to change. Therefore, personnel planning is becoming increasingly important for companies, due to the globalization of new technology and organizational change processes overshadowing organizational life repeatedly. Organizations that are not supported by employees which is in accordance with the quantity, quality, strategy and function that is good, of course the organization will find it difficult to maintain and develop its existence in the future, so that personal planning is successful. Influencing factors hi environmental factors, organizational decisions, employee supply factors.